2023
DOI: 10.1167/jov.23.8.11
|View full text |Cite
|
Sign up to set email alerts
|

Faces in scenes attract rapid saccades

Abstract: During natural vision, the human visual system has to process upcoming eye movements in parallel to currently fixated stimuli. Saccades targeting isolated faces are known to have lower latency and higher velocity, but it is unclear how this generalizes to the natural cycle of saccades and fixations during free-viewing of complex scenes. To which degree can the visual system process high-level features of extrafoveal stimuli when they are embedded in visual clutter and compete with concurrent foveal input? Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Recent research from our lab found that saccades targeting faces during free-viewing are preceded by shorter fixation durations compared to saccades directed toward inanimate objects (Borovska & de Haas, 2023). This suggests the latency advantage for face-directed saccades generalizes between the SRT and natural free-viewing and at least some mechanisms of face salience may be shared between the SRT and free-viewing.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recent research from our lab found that saccades targeting faces during free-viewing are preceded by shorter fixation durations compared to saccades directed toward inanimate objects (Borovska & de Haas, 2023). This suggests the latency advantage for face-directed saccades generalizes between the SRT and natural free-viewing and at least some mechanisms of face salience may be shared between the SRT and free-viewing.…”
Section: Introductionmentioning
confidence: 78%
“…We recently found that fixations preceding saccades towards faces in complex natural scenes have a shorter duration than fixations preceding saccades towards inanimate objects (Borovska & de Haas, 2023). This suggests that the mechanisms mediating lower saccadic reaction times in the Saccadic Choice Paradigm may be at play during free viewing and potentially contribute to face salience in complex scenes.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that fixations preceding saccades toward faces in complex natural scenes have a shorter duration than fixations preceding saccades toward inanimate objects ( Borovska & de Haas, 2023 ). This finding suggests that the mechanisms mediating lower SRTs in the saccadic choice paradigm may be at play during free viewing and potentially contribute to face salience in complex scenes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research from our lab found that saccades targeting faces during free viewing are preceded by shorter fixation durations compared with saccades directed toward inanimate objects ( Borovska & de Haas, 2023 ). This finding suggests the latency advantage for face-directed saccades generalizes between the SRT and natural free viewing, and that at least some mechanisms of face salience may be shared between the SRT and free viewing.…”
Section: Introductionmentioning
confidence: 99%